(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
This article discusses people who are prone to bad habits, the appearance of habits, the reasons for their occurrence, their appearance, people prone to bad habits in the process of carrying out our activities, such as prohibition, restriction, explanation, assistance, personal example work with interrelated styles is highlighted.